MODEL PRODUKTIVITAS PROSES PRODUKSI BIOETANOL PADA BIOREAKTOR AEROBIK DAN ANAEROBIK SINAMBUNG - Irvan S. Kartawiria, Khaswar Syamsu, Erliza Noor, Evita H. Legowo (Jurnal Teknologi Industri Pertanian, 2016)
One of the issues in bioethanol production as fuel is the low productivity of fermentation process. Application of serial continuous bioreactor could increase the fermentation productivity. Series of bioreactor running in aerobic condition followed by anaerobic fermentation may resolve cell exhaustion and low substrate utilization problems, as pre-conditioned fresh cell cultured in aerobic bioreactor is fed continuously to fermentation tank. This research studied the productivity model of such configuration and its limitation in bioethanol production. The model developed was based on unstructured growth model applied on process mass balance on steady state. Model validation and verification were conducted in 2000 mL CSTR (Continuously Stirred Tank Reactor) type experimental bioreactor, utilizing Saccharomyces cerevisiae ATCC18824 in nutrient broth. Glucose 20% w/v was used as carbon source in feed stream. Process kinetics and product formation were observed by measuring biomass using spectrophotometry, glucose by DNS method and ethanol produced by HPLC. The results show that model could be developed by deriving mass balance for the system, with adjustment where μ is following modified Monod equation. The model accuracy was 82.43 ± 1.58% in term of ethanol productivity. Productivity of ethanol was observed as a function of cell concentration in aerobic bioreactor (X1) and dilution rate at anaerobic bioreactor (D2) and its interaction was observed through the central composite design. Highest productivity of 19.01g/L.h was observed at optimized value ofX1 22g/l and D20.30 h-1 with the yield of YP/Stotal of 0.36 g ethanol/ g sugar, while fermentative yield was 0.45 g ethanol/ g sugar.The value wa higher than productivity in batch fermentation at the same working volume of bioreactor (1.01g/L.h). Overall substrate conversion on highest productivity was 87.65%, where 61.08% substrate converted into bioethanol.Keywords: bioethanol,continuous bioreactor, productivity model